Hubungan Kesesakan dan Kontrol Diri dengan Kecenderungan Agresi Masyarakat Dikawasan Padat Penduduk Kota Surabaya - Handayani, Suci Lestari (Universitas Pendidikan Ganesha, 2020)
The number of cases of violence occurring in big cities such as Surabaya is partly due to the density of the area due to population growth. The population of the population causes congestion and has the effect of changing one's attitude. The purpose of this study was to examine the relationship between tightness and self-control with the tendency of communist aggression in densely populated areas of the city of Surabaya. This type of research is descriptive quantitative research. The population of this research is the people who live in the densely populated city of Surabaya. The number of samples consisted of 85 people between the ages of 16 and 55. The sample criteria were determined to be around 16 years to 55 years. From the results of hypothesis testing that has been done, it is found that H0 and Ha are accepted, it can be seen that the F value is 0.93081 with the Sig. 0.00 indicates that distress and self-control affect aggression. The contribution of the influence of distress and self-control can be seen from the value of the coefficient of determination (R2) based on the calculation results, the R2 value is 0.687. This means that the stress and self-control impact on people's attitudes of anger is 68.7% and the remaining 31.3% are influenced by other factors that are not explained in this study.